Pengembangan Dan Implementasi Aplikasi Pencarian Lokasi Pelanggan Dan Penjadwalan Teknisi PT. Telkom Kandatel Pati Berbasis Android - Tri Nor Ahfandi; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
Telkom Group is the only telecommunications company as well as telecommunications service providers and the largest network in Indonesia. At this time the daily scheduling of technicians and customers do not have a location search memadahi information system. In some fields, the management is still done manually. Such as scheduling repairs to the customer given to technicians only reports of damage on the day yesterday so that customers in today's report will have to wait one day plus also a technician who does not mengetehaui in detail the work area so that slowing customer service. Development of information systems in this study using the waterfall method. The waterfall model is composed of: requirements, design, implementation, testing and maintenance. For the beginning of the design, developers need observation or interviews to determine the needs of the system that is being developed. Applications developed using CodeIgniter framework. The results of this final project is an information system that can meet the needs of PT. Telkom Kandatel Patis in managing daily scheduling service technicians and search customer locations in accordance with existing business processes.